Representation in Danish Local Politics - Hvidkjær, Marc Sabatier; Larsen, Martin Vinæs (Politica, 2025)
Local politicians play a pivotal role in Danish democracy, but we know little about how well they represent their constituents. This is difficult to study, as it requires comparable data on the political preferences of politicians and voters. We overcome this issue by comparing the attitudes of local politicians on a wide range of local political items given to a Voting Advice Application before the 2021 municipal election to a nationally representative survey we fielded in 2023 (n = 28,817). We find a strong relationship between citizen and politician preferences across local issues and municipalities. We also examine whether homeowners are better represented than renters. This is not the case, as owners and renters mostly agree on local policy and are represented proportionally to their share of the population.